Gerakan Siaga Masyarakat Anti-Diabetes Mellitus (SIMANIS) Melalui Kartu SIDIA (Skrining Pre-Diabetes) di Kabupaten Semarang - Lukman Fauzi; R.R. Sri Ratna Rahayu; Lindra Anggorowati; Hendri Hariyanto; Trinita Septi Mentari; Lia Diah Kumalasari; Rina Sulistiana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Diabetes Mellitus (DM) is a non-communicable disease that contributes to the cause of death. Based on the analysis of the situation in Kawengen Village, Semarang Regency, there were several problems related to the incidence of DM, including the Non-Communicable Disease Integrated Guidance Post Program (Posbindu PTM), which was not running optimally. Based on these problems, it is necessary to form a movement called the Anti-Diabetes Mellitus Community Alert Movement (SIMANIS). Active case finding and detection of pre-DM cases aim to capture people who already have pre-DM symptoms, but they do not know. Furthermore, if caught, they can be followed up so that they are willing to go to the health service unit before complications occur. The implementation of this community service activity is carried out in four stages, namely the formation of SIMANIS cadres, education on prevention and control of DM to SIMANIS cadres and the community, ToT on how to fill in and use the SIDIA Card (pre-diabetes screening) to SIMANIS cadres, and use of the SIDIA Card for early detection active case finding pre-DM. There was an increase in the pre-post education knowledge score from 7.59 + 1.5 to 8.93 + 0.9 and an increase in the pre-post education attitude score from 7.96 + 1.22 to 9.07 + 0.78. SIMANIS through the use of the SIDIA Card can be used to increase public awareness in prevention, early detection, and case finding of DM.